Al-Manâr de 1925 à 1935 : la dernière décennie d'un engagement intellectuel - Nadia Elissa-Mondeguer (Revue des Mondes Musulmans et de la Méditerranée)
The last ten years of the publication of al-Manâr, the journal par excellence of Muslim reformism, attests to the participation of the journal in the intense intellectual life in the Middle East during the interwar period. These last ten years represent a corpus often volumes, almost one-third of the entire collection (35 volumes). The involvement of the journal in contemporary debates began in March 1898 with the publication of its first issue in Egypt ; the journal ceased shortly after the death in July 1935 of its founder, the Syrian 'âlim, Muhammad Rashîd Ridâ. The journal, itself, was a result of Rashîd Ridâ's acquaintance with shaykh Muhammad 'Abduh (d. 1905), the emblematic figure, along with Jamâl al-Dîn al-Afghânî (d. 1897), of reformist thought in the late 19th century. After the death of these two pioneers of the Salafiyya movement, this monthly Islamic journal spoke about, guided and shaped Salafi doctrine which preached a return to the original precepts of Islam in order to create a modern society. The term "reform" (islâh), before being enduringly tied to Islamic movements, was the leading idea behind the entire Ottoman liberal thought before the First World War, including Salafi thought. Between the two World Wars, the idea of « renewal » (tajdid) became the essential term of that time. Tajdid was therefore the main concept in the interwar period, although its correlative term « renovator » (mujaddid) belonged to traditional Islamic terminology. For Rashîd Ridâ, both terms, islâh and tajdid, became interchangeable. Challenging the monopoly of the term tajdid by Westernised intellectuals, Ridâ sees himself as the eulogist of a veritable revival of Islam.